Reforming public financial management systems in developing countries as a contribution to the improvement of governance - Stephan Klingebiel; Timo Casjen Mahn (Deutsches Institut für Entwicklungspolitik (DIE), 2011)
How does reforming public financial management (PFM) help to improve governance in developing countries? In both industrialised and developing countriesPFM reforms affect fundamental interests of state andgovernance. Although PFM has steadily grown in importancein development cooperation in recent yearsand such donors as the United Kingdom and Germanyare increasing their engagement in this respect, PFMreforms – such as the strengthening of national auditoffices and the introduction of IT-assisted financialmanagement systems – are still not seen as a separatearea of activity, but frequently from the narrow angleof improving technical efficiency. For PFM reforms tosucceed, however, it is vital that their effects on governance are taken into account. The increased use of modern development cooperationapproaches based on the Paris Declaration principleshas led to an interest being taken in the qualityand efficiency of PFM systems that goes well beyond a direct interest in preventing corruption. Above all,standardised assessment tools have made it possiblefor the quality of PFM systems to be measured systematically in many developing countries and for moretargeted reform programmes to be implemented. However, the contribution made by PFM reforms to the improvement of governance is often underestimated. Four basic dimensions of governance benefit from PFM reforms: A functioning system of PFM makes actors more accountable to the parliament, the national audit office and the public. Established PFM structures encourage the separation of powers by seeking to build institutions that are based on a division of labour and equipped with control mechanisms. PFM reforms help to improve transparency by generating information, by networking sources of information and by making them accessible, this also being a prerequisite for crucial governance reforms, such as decentralisation processes. PFM processes improve the effectiveness and efficiency of government action and so increase the state's legitimacy. The following conclusions can be drawn: first, it is important to promote such “pioneering institutions” as national audit offices to narrow the gap between de jure and de facto reforms. Second, the principles called for in the context of PFM reform programmes, such as the transparency of budgets and open tendering and procurement procedures, must also be reflected in development cooperation programming itself. Third, PFM reform programmes should be guided by the country's need for reform rather than any fiduciary requirements donors may have. Fourth, development cooperation should be so designed that any adverse effects it may have on governance in developing countries – such as the poaching of qualified government staff for donor projects – are kept to a minimum.
Keywords: 330